Dynamic capabilities and organizational ambidexterity: New strategies from emerging market multinational enterprises in Nigeria. (12th March 2022) - Ochie, Chinedu; Nyuur, Richard B.; Ludwig, Greg; Cunningham, James A.
Abstract: This study examines the strategies that firms deploy in developing and scaling up organizational ambidexterity under conditions of environmental uncertainty. Using five emerging market multinational enterprises (EMNEs) in the Nigerian financial sector as case studies the study provides a framework of four main ambidextrous strategies deployed by these firms. Based on the dynamic capabilities' lens, the study found that EMNEs pursue a combination of contextual and structural ambidextrous strategies, including new business models, investment in technology for strategic innovation, developing strategic alliances, and internationalization. These strategies serve as levers of dynamic capabilities for fostering exploration of new business opportunities, while strengthening, enriching, and exploiting their existing capabilities. These findings contribute to enriching the existing literature on ambidexterity by contributing to the ongoing debate about how ambidexterity manifest in EMNEs during periods of environmental uncertainty, particularly from an emerging country context.